Quantity as a Fish Views It: Behavior and Neurobiology - Messina, Andrea; Potrich, Davide; Perrino, Matilde; Sheardown, Eva; Miletto Petrazzini, Maria Elena; Luu, Peter; Nadtochiy, Anna; Truong, Thai V.; Sovrano, Valeria Anna; Fraser, Scott E.; Brennan, Caroline H.; Vallortigara, Giorgio (Frontiers in Neuroanatomy, 2022)
An ability to estimate quantities, such as the number of conspecifics or the size of a predator, has been reported in vertebrates. Fish, in particular zebrafish, may be instrumental in advancing the understanding of magnitude cognition. We review here the behavioral studies that have described the ecological relevance of quantity estimation in fish and the current status of the research aimed at investigating the neurobiological bases of these abilities. By combining behavioral methods with molecular genetics and calcium imaging, the involvement of the retina and the optic tectum has been documented for the estimation of continuous quantities in the larval and adult zebrafish brain, and the contributions of the thalamus and the dorsal-central pallium for discrete magnitude estimation in the adult zebrafish brain. Evidence for basic circuitry can now be complemented and extended to research that make use of transgenic lines to deepen our understanding of quantity cognition at genetic and molecular levels.